No Differences in Nasal Tissue Inflammatory Cells and Adhesion Molecules (iCAM-1 and vCAM-1) Based on the Comparison of EGPA With Eosinophilic Chronic Sinusitis With Polyposis. Issue 4 (July 2019) - Brescia, Giuseppe; Schiavon, Franco; Nicolè, Lorenzo; Zanoletti, Elisabetta; Zanotti, Claudia; Padoan, Roberto; Felicetti, Mara; Parrino, Daniela; Cinetto, Francesco; Cangiano, Daniela; Giacomelli, Luciano; Cappellesso, Rocco; et al.
Background: An example of aggressive eosinophilic polyposis can be found in eosinophilic granulomatosis with polyangiitis (EGPA). Intercellular adhesion molecule-1 (iCAM-1) and vascular cell adhesion molecule-1 (vCAM-1) play a part in mediating the recruitment and adhesion of leukocytes to the vessel wall, and their blood-to-tissue migration under inflammatory conditions. Objective: This prospective study compared 3 groups—patients with a definite diagnosis EGPA, non-EGPA patients with phenotypic features suggestive of EGPA, and patients with non-eosinophilic nasal polyposis (controls)—in terms of nasal tissue histology, iCAM-1 and vCAM-1 expression, and blood inflammatory cells. Methods: A total of 58 adults underwent sinus surgery (13 patients with EGPA, 23 suspected of having EGPA, and 22 controls). Results: Mean tissue eosinophil counts were significantly higher in EGPA patients and suspected cases of EGPA than in controls. Although iCAM-1 and vCAM-1 were diffusely expressed in sinonasal tissues, they did not differently stain EGPA, eosinophilic-type and non-eosinophilic polyposis. Blood basophil and eosinophil levels were high in both the EGPA and the suspected EGPA groups. Intergroup differences were found for eosinophils but not for basophils. Conclusions: We do not have yet blood or tissue markers able to differentiate the early phase of EGPA from chronic rhinosinusitis with nasal polyps. Further investigations are mandatory considering EGPA patients at their initial diagnosis and before any treatment, in terms of nasal histology and blood inflammatory cells, to identify markers characterizing sinonasal mucosa inflammation and useful for an early diagnosis of EGPA.